Development of driving cycle under real world traffic conditions: A case study - Geetha A.; Subramani C. (Institute of Advanced Engineering and Science, 2019)
The modeling of a car is essentially done by taking into consideration the driving terrain, traffic conditions, driver’s behavior and various other factors which may directly or indirectly affect the vehicle’s performance. A vehicle is modeled for given specifications and constraints like maximum speed, maximum acceleration, and braking time, appropriate suspension for the gradient of the road and fuel consumption. Henceforth, a profound study and analysis of different drive cycles are essential. A time dependent drive cycle is a condensed form of data that helps us to determine the time taken to conduct the driving test on the road. This article highlights the development of a real driving cycle in the area of Tamilnadu, India. On-road vehicle’s speeds versus time data were obtained along the selected route. The data obtained were analyzed first and then a new driving cycle was developed.